Analysis of Hydrodynamic Characteristics of Semi-Enclosed Harbors—a Cause Study of Xiangzhou Port - YANG Yugui; XUAN Xiaoming; LIU Guozhen; TONG Xiaolei; YUAN Fei (Renmin Zhujiang)
Affected by the construction of a series of projects,the semi-enclosed harbor often appears the phenomenon of weakening hydrodynamic force and worsening water exchange.In order to study the impact of project construction on the hydrodynamic environment of semi-closed harbors,a typical semi-enclosed port,namely Xiangzhou Fishing Port,in the Pearl River Estuary was taken as an example,and the impact of detailed control planning of the surrounding areas on flood discharge,tidal influx,and water exchange in Xiangzhou Fishing Port was studied.The results show that after the implementation of the planning scheme,the water level of the water area near the planning area and the upstream entrance gate,as well as the tidal volume of the tidal channel on the west side of Lingdingyang change slightly,but the tidal volume in the area of Xiangzhou Port decreases by about 1%.The hydrodynamic force is further weakened,and the semi-exchange cycle of the water body increases by about 3.2%.In particular,the water exchange capacity in the northwest corner of the port area is relatively poor,which is unfavorable to the water environment for a long time,and it is necessary to take hydrodynamic enhancement measures.The research results can provide a reference for hydrodynamic improvement in the water area of Xiangzhou Port.